“Facemasks with TUL”: Science and Ethics in Liminality - Jetmarová, Jana; Trčka, Michal (Teorie vědy / Theory of Science, 2023)
The text presents the results of a qualitative study focused on the issue of using nanomaterials in the extraordinary circumstances linked to the COVID-19 pandemic, particularly referring to the “Roušky s TULkou” initiative. Within several weeks, this initiative managed to launch the production of highly efficient nanofiber filters using the original AC Electrospinning technology on an industrial scale. The goal of the research was to analyse both the regional experience and the value-based challenges, conflicts and ethical dilemmas posed by an emergency situation. The theoretical starting points of the research were the Turnerian understanding of liminality, communitas and antistructure and Stenner’s concept of liminal spaces. The results of the research show that the pandemic situation contributed to the emergence of an unexpected potential of the new technology and that the realisation of the activity was influenced not only by know-how and the university’s technical facilities, but particularly by social capital, thus uncovering the potential of the anti-structural character of the initiative and the temporary suspension of hierarchically established university structures.